The Effect Of Complex Chemical Additives on Foam and Its Properties - Mirzaev Bakhodir Kozibaevich; Otakulov Bakhromjon Adhamovich; Mamatov Khamidulla Abdullaevich; Abdug'aniev Numonjon Nabijonovich; Solijonov Hojiakbar Solijon o‘g‘li; Majidova Guchehra Abdumuxtor qizi (Genius Journals, 2023)
The effect of complex chemical additives on foam foaming, foam stability, hardening and other properties is studied in the article.
Keywords: Foam; mixture; component; bubbles